Calcium, an Emerging Intracellular Messenger for the Hippo Pathway Regulation - Wei, Yiju; Li, Wei (Frontiers in Cell and Developmental Biology, 2021)
The Hippo pathway is a conserved signaling network regulating organ development and tissue homeostasis. Dysfunction of this pathway may lead to various diseases, such as regeneration defect and cancer. Studies over the past decade have found various extracellular and intracellular signals that can regulate this pathway. Among them, calcium (Ca2+) is emerging as a potential messenger that can transduce certain signals, such as the mechanical cue, to the main signaling machinery. In this process, rearrangement of the actin cytoskeleton, such as calcium-activated actin reset (CaAR), may construct actin filaments at the cell cortex or other subcellular domains that provide a scaffold to launch Hippo pathway activators. This article will review studies demonstrating Ca2+-mediated Hippo pathway modulation and discuss its implication in understanding the role of actin cytoskeleton in regulating the Hippo pathway.